Abrasion resistance and mechanical properties of self-compacting concrete with different dosages of fly ash/silica fume - Turk, Kazim; Karatas, Mehmet (Natl Inst Science Communication-Niscair, 2011)
In this study, nine different types of concrete were adopted: vibrated traditional concrete (VTC) with low slump (68 mm) and eight types of self-compacting concrete (SCC) in which cement was partially replaced by four kinds of replacements (25%, 30%, 35% and 40%) of class F fly ash (FA) and by four kinds of replacements (5%, 10%, 15% and 20%) of silica fume (SF). The main objective of this research was to evaluate the effect of different types and dosages of mineral additions on the mechanical properties and abrasion resistance of SCC. Compressive, splitting tensile strength and UPV tests were conducted for the ages of 3, 28 and 130 days whilst the modulus of elasticity and the abrasion resistance tests were performed for 28 days. Consequently, it was found that although the compressive and tensile strength and the UPV values of SCC specimens were higher generally than those of VTC specimens for all curing ages, the compressive strength and the UPV values of SCC specimens decreased for 3 days when FA and SF content increased. The modulus of elasticity of SCC specimens with SF in general increased with an increase in SF content whilst the modulus of elasticity decreased with an increase in FA content. Moreover, it was concluded that increasing SF content more improved the abrasion resistance of SCC compared to FA whilst the abrasion resistance of all SCC specimens was higher than that of VTC. On the other hand, there was a strong correlation, which is not dependent on the mineral admixture type and content, between the wear loss with compressive strength and the elasticity modulus for SCC specimens.
Keywords: Self-compacting concrete; Silica fume; Fly ash; Mechanical properties; Abrasion resistance